Chemical Composition, Antifungal and Antibiofilm Activities of the Essential Oil of Mentha piperita L. (13th December 2012) - Saharkhiz, Mohammad Jamal; Motamedi, Marjan; Zomorodian, Kamiar; Pakshir, Keyvan; Miri, Ramin; Hemyari, Kimia
Abstract : Variations in quantity and quality of essential oil (EO) from the aerial parts of cultivated Mentha piperita were determined. The EO of air-dried sample was obtained by a hydrodistillation method and analyzed by a gas chromatography/mass spectrometry (GC/MS). The antifungal activity of the EO was investigated by broth microdilution methods as recommended by Clinical and Laboratory Standards Institute. A biofilm formation inhibition was measured by using an XTT reduction assay. Menthol (53.28%) was the major compound of the EO followed by Menthyl acetate (15.1%) and Menthofuran (11.18%). The EO exhibited strong antifungal activities against the examined fungi at concentrations ranging from 0.12 to 8.0 μ L/mL. In addition, the EO inhibited the biofilm formation of Candida albicans and C. dubliniensis at concentrations up to 2 μ L/mL. Considering the wide range of the antifungal activities of the examined EO, it might be potentially used in the management of fungal infections or in the extension of the shelf life of food products.